2013
DOI: 10.1089/zeb.2013.0891
|View full text |Cite
|
Sign up to set email alerts
|

Feed and Feeding Regime Affect Growth Rate and Gonadosomatic Index of Adult Zebrafish (Danio Rerio)

Abstract: A 5-week study was conducted to evaluate commercially available Artemia, Ziegler zebrafish diet, and Calamac diet fed in five different feeding regimes on the growth and reproductive development of 7-month-old zebrafish. Zebrafish were fed to satiation three times daily during the normal work week and twice daily during the weekend and holidays. Zebrafish in dietary groups CCC (Calamac three times daily) and CCA (Calamac twice daily, Artemia once daily) had a significantly ( p < 0.05) greater weight gain and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 59 publications
3
17
1
Order By: Relevance
“…A proximate analysis revealed considerable differences in crude protein, fat, fiber, and carbohydrate content among the diets tested in this study, indicating substantial variation in nutrient profiles among these feeds. Our data, along with results from previous studies, [64][65][66][67][68] clearly demonstrate that variations in dietary ingredients and corresponding nutrient composition among commercially available Negative coefficients represent a lower spawning probability or lower predicted value relative to Artemia, whereas positive coefficients represent a higher spawning probability or higher predicted value. Dependent variables: spawning success = probability of successful spawn; total egg production = predicted mean clutch size; embryo viability = mean predicted proportion of viable embryos within a clutch.…”
Section: Influence Of Diet On Metrics Of Zebrafish Health 515supporting
confidence: 77%
“…A proximate analysis revealed considerable differences in crude protein, fat, fiber, and carbohydrate content among the diets tested in this study, indicating substantial variation in nutrient profiles among these feeds. Our data, along with results from previous studies, [64][65][66][67][68] clearly demonstrate that variations in dietary ingredients and corresponding nutrient composition among commercially available Negative coefficients represent a lower spawning probability or lower predicted value relative to Artemia, whereas positive coefficients represent a higher spawning probability or higher predicted value. Dependent variables: spawning success = probability of successful spawn; total egg production = predicted mean clutch size; embryo viability = mean predicted proportion of viable embryos within a clutch.…”
Section: Influence Of Diet On Metrics Of Zebrafish Health 515supporting
confidence: 77%
“…The present study also gets some support from the work of Bahnasawy (), who reported that the weight gain and specific growth rate in Nile tilapia fed with 170 g kg −1 , 300 g kg −1 and 350 g kg −1 crude protein diet increased significantly with increasing dietary protein level. In contrast to present findings, Gonzales & Law () found that zebrafish fed daily with three time commercial diet and in combination with one time Artemia had a significantly ( P < 0.05) greater weight gain and specific growth rate as compared to only Artemia and with one time commercial diet.…”
Section: Discussioncontrasting
confidence: 99%
“…The ovary exerts influence on the body weight of females, due to the occupation of a large part of the celomatic cavity, demonstrated by the gonadosomatic index. The results found for the gonadosomatic index were within the values described for zebrafish by Chang et al (2013) and Gonzales & Law (2013) in their control treatments, with values close to 1% for males and 13% for females.…”
Section: Discussionsupporting
confidence: 82%